Students’ Perception on the Use of YouTube for Students’ Speaking Skill at SMAN 8 Kota Jambi - Nuryanti, Anisyah; Silfia, Efa; Aisyah, Siti (JELT: Journal of English Language Teaching, 2024)
This research aims to know how the students’ perception when they using of YouTube for their speaking skill. The research using a Qualitative Design with the Phenomenology Approach, utilizing qualitative data in the form of a descriptive qualitative. With tenth students present during data collection. Purposive sampling is employed to select subjects, and the research instruments include a observation, interview, and documentation. The technique of data collection used steps are data reduction, coding, data display, and conclusion. The findings reveal that students use YouTube as an additional English learning media, students can communicate with teacher if the teacher encourage them to speak English, the students can pronounce good when they speak, the vocabulary they used is a new, the students still not fluent when they speak English because they still think of the grammar. The results of the research is students perception on the use of YouTube for learn English is positive, in YouTube they can learn anything especially for speaking skills. In YouTube can make students good pronounce, increase students vocabulary, but YouTube less helpful for grammar and fluent.Keywords : Students’ Perception, YouTube, Speaking Skill